Decode-and-Forward Relaying for Cooperative NOMA Systems With Direct Links - Liu, Hongwu; Ding, Zhiguo; Kim, Kyeong Jin; Kwak, Kyung Sup; Poor, H. Vincent (IEEE transactions on wireless communications, 2018)
This paper investigates a cooperative non-orthogonal multiple access system, in which a base station communicates with two far users with the aid of a decode-and-forward (DF) relay. Three cooperative relaying schemes, namely, the fixed relaying (FR), the selective DF with coordinated direct and relay transmission (SDF-CDRT), and the incremental-selective DF (ISDF) relaying are proposed to enhance the outage performance for the two far users by utilizing both the direct and relay links. Taking into account the received signal-to-noise ratio (SNR) events at the relay, the SDF-CDRT scheme adaptively forms an orthogonal transmission branch with respect to the direct link or keeps silent to reduce error propagation. Besides considering the relay detection results, the ISDF scheme further exploits the limited feedback of the received SNR events from two users, so that error propagation can be avoided and unnecessary relaying can be reduced. Analytical expressions for the outage probabilities and average throughputs of the paired users are derived in closed-form for the three cooperative relaying schemes. Asymptotic expressions for the outage probabilities are derived in the high SNR region. It is shown that the FR and SDF-CDRT schemes achieve a diversity order of one for both users, while the ISDF scheme achieves a diversity order of two for both users. The superior system performance achieved by the proposed schemes over those of the existing methods is verified by Monte Carlo simulations.